Photopic & scotopic light perception - Bell, Michelle A. (Kansas State University, 2010)
This paper discusses photopic and scotopic vision of the human eye and the implications that could result in the design process of the lighting industry. The incorporation of scotopic vision in lighting effects the perceived illumination in all settings; but these affects and benefits are seen more prevalently at night, as this is when scotopic vision is utilized by the eye the most. The paper will begin with an overview of the eye including discussions of exactly what photopic and scotopic vision are, as well as how the eye works. This will lay a foundation for the paper to help the reader better comprehend and understand the remainder of the content. After the groundwork has been laid, the factors that affect how the eye perceives light will be discussed. These factors include pupil size and color of the light. A discussion of the basis for current lighting industry design and how light levels are measured will follow. Once these topics have been fully explored, there will be a discussion of the changes that could occur in the lighting industry if scotopic vision is taken into account. Increased energy efficiency would result if the scotopic vision is incorporated, resulting from the decrease in needed total lumen output. There have been a few applications that have utilized the effects of the scotopic vision in their design, these cases will be presented. Following the case study discussions, will be a discussion of a survey conducted by myself on the change-out of high pressure sodium (HPS) fixtures to LED fixtures in the downtown Poyntz Avenue area of Manhattan, KS. After all studies have been reviewed, conclusions and correlations among them will be explored. Following this analysis, suggestions will be given to improve the way lighting is designed in the industry.
Keywords: scotopic; night lighting; LED; efficiency; scotopically enhanced; pupil lumens; Architecture (0729); Engineering, Civil (0543); Engineering, Electronics and Electrical (0544); Environmental Sciences (0768)